FAKTOR PENENTU LOYALITAS MEREK PADA KOPI PANDAWA DI INDONESIA - Lely Afiati; Liesta Verawati; Muhamad Syaeful Anwar (POLITEKNIK LP3I JAKARTA, 2024)
This research was conducted to assess the factors that influence brand loyalty for Pandawa ground coffee in Indonesia. This research aims to determine the influence of brand image, brand loyalty, brand awareness, and brand experience, both partially and simultaneously, on online customer brand loyalty at Kopi Pandawa in Indonesia. The sample used was 100 people, namely people who had bought Pandawa ground coffee online. The data analysis technique used is a multiple regression analysis technique using the SPSS version 25 application to process the data. The research results show that for the simultaneous test, the variables brand image, brand trust, brand awareness, and brand experience together have a positive and significant effect on brand loyalty for Pandawa coffee in Indonesia. In a partial test, the brand image variable has a negative and significant effect on brand loyalty in Pandawa coffee. The brand trust variable has a negative and significant effect on brand loyalty in Pandawa coffee. The brand awareness variable has a positive but not significant effect on brand loyalty for Pandawa coffee. Meanwhile, the brand experience variable has a positive and significant effect on brand loyalty for Pandawa coffee.